MAGHREB LITERATURE OF FRENCH EXPRESSION - Yakhyokoulova, N.Sh. (PT. Antis International Publisher, 2024)
Francophone Algerian literature is part of a special socio-historical and cultural context that determined its emergence under French colonization. Indeed, it was this French settlement that gave rise to the development of a very important element - the French language, which would later be used to condemn and challenge this occupation through literary texts. Moreover, French-language Algerian literature, born from the writing models adopted in the French school during colonization, would gradually move away from them to create its own literary field with new values as well as different aesthetic categories